Toward Computational Models of Multilingual Sentence Processing. Issue 1 (13th May 2020) - Frank, Stefan L.
Abstract: Although computational models can simulate aspects of human sentence processing, research on this topic has remained almost exclusively limited to the single language case. The current review presents an overview of the state of the art in computational cognitive models of sentence processing, and discusses how recent sentence‐processing models can be used to study bi‐ and multilingualism. Recent results from cognitive modeling and computational linguistics suggest that phenomena specific to bilingualism can emerge from systems that have no dedicated components for handling multiple languages. Hence, accounting for human bi‐/multilingualism may not require models that are much more sophisticated than those for the monolingual case. Abstract :